Advances in understanding the interaction between Solanaceae NLR resistance proteins and the viral effector Avr - Jianming Wei; Yunzhou Li; Xiangru Chen; Ping Tan; Tayeb Muhammad; Yan Liang (Plant Signaling & Behavior, 2024)
The rising prevalence of viral-induced diseases, particularly those caused by certain strains, poses a substantial risk to the genetic diversity of Solanaceae crops and the overall safety of horticultural produce. According to the “gene-for-gene” hypothesis, resistance proteins are capable of selectively identifying nontoxic effectors produced by pathogens, as they are under purview of the host’s immune defenses. The sensitivity and responsiveness of Solanaceae plants to viral attacks play a crucial role in shaping the outcomes of their interactions with viruses. Pathogenic organisms, devise an array of infection tactics aimed at circumventing or neutralizing the host’s immune defenses to facilitate effective invasion. The invasion often accomplishes by suppressing or disrupting the host’s defensive mechanisms or immune signals, which are integral to the infection strategies of such invading pathogens. This comprehensive review delves into the myriad approaches that pathogenic viruses employ to infiltrate and overcome the sophisticated immune system of tomatoes. Furthermore, the review explores the possibility of utilizing these viral strategies to bolster the resilience of horticultural crops, presenting a hopeful direction for forthcoming progress in plant health and agricultural stability.